Kontribusi Unit Usaha Pesantren dalam Meningkatkan Kemandirian Ekonomi Pesantren - Diah Ayu Septianingsih; Misfi Laili Rohmi (Budgeting: Jurnal Akuntansi Syariah, 2023)
Islamic boarding schools are one of the Islamic educational institutions. Initially, pesantren were traditional in nature to study Islamic religious knowledge as a way of life (Tafaqquh Fi Al-din) which emphasized the importance of morality in society, but were also institutions that created superior human resources and were able to create independence. In line with this, the Baitunnur Islamic Boarding School is a pesantren that not only provides education in the religious field, but also provides educational knowledge in the economic field by teaching entrepreneurship. The Baitunnur Islamic Boarding School has four business units, namely the santri convection, the santri cooperative, the gallon depot, and the santri barbershop. This type of research is field research (Field Research) conducted at the Baitunnur Tanggulangin Punggur Islamic Boarding School, Central Lampung. Sources of data in this study are primary data sources, namely from old foundations, business unit managers, students and alumni who participate in entrepreneurial activities and secondary data sources in the form of books, journals and documents relevant to research. Meanwhile, data collection techniques used observation, interviews, and documentation. The data validity guarantee technique uses the comfirmability method. The data analysis technique is through data reduction, data presentation, as well as verification and drawing conclusions. Based on the results of research conducted by researchers regarding the Role of Islamic Boarding School Business Units in Islamic Boarding School Economic Independence at Baitunnur Tanggulangin Punggur Central Lampung, it can be concluded that the role of business units in Islamic boarding schools' economic independence at Baitunnur Islamic Boarding School has been going well. This can be seen from the Islamic boarding schools that provide a forum for students to develop their skills to build a business or business, provide job opportunities through business unit activities and continue to fulfill and carry out Islamic boarding school activities even though they are not assisted by donors.